2022
DOI: 10.3934/neuroscience.2022010
|View full text |Cite
|
Sign up to set email alerts
|

Encephalomalacia/gliosis, deep venous thrombosis, and cancer in Arg393His antithrombin Hanoi and the potential impact of the β-amyloid precursor protein (APP) on thrombosis and cancer

Abstract: <abstract> <p>A heterozygous Arg393His point mutation at the reactive site of antithrombin (AT) gene causing thrombosis in a Vietnamese patient is reported and named as Arg393His in AT-Hanoi. The present variant is characterized by a severe reduction of functionally active AT plasma concentration to 42% of normal resulting in multiple severe thrombotic events such as cerebral venous thrombosis (CVT) (encephalomalacia/gliosis), recurrent deep venous thrombosis (DVT) and the development of kidney can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 137 publications
0
1
0
Order By: Relevance
“…Our study identified several complement system-related genes in AD. Among the 23 genes previous studies have shown their correlation with AD, we have: GFAP [ 41 , 42 ], PDGFRβ [ 43 45 ], NFKBIA [ 46 ], TNFRSF1B [ 47 ], NOTCH1 [ 48 ], BCL6 [ 49 ], CSF1R [ 50 ], LEP [ 51 ], DCLRE1C [ 52 ], KCNJ10 [ 53 ], MAP2K1 [ 54 ], VIP [ 55 ], SNCA [ 56 ], ENO2 [ 57 ], SST [ 58 ], UCHL1 [ 59 ], HPRT1 [ 60 ], STAT4 [ 61 ], CD14 [ 62 ], ITGB2 [ 63 ], SPP1 [ 64 ], STX1A [ 65 ], and SYP [ 66 ]. And these genes are involved in the regulation of molecules associated with the complement system, for instance, GFAP [ 67 ], PDGFRβ [ 68 ], NFKBIA [ 69 ], TNFRSF1B [ 70 ], NOTCH1 [ 71 ], BCL6 [ 72 ], CSF1R [ 73 ], LEP [ 74 ], DCLRE1C [ 75 ], KCNJ10 [ 76 ], MAP2K1 [ 77 ], VIP [ 78 ], SNCA [ 79 ], ENO2 [ 80 ], SST [ 81 ], UCHL1 [ 82 ], HPRT1 [ 83 ], STAT4 [ 84 ], CD14 [ 85 ], ITGB2 [ 86 ], SPP1 [ 87 ], STX1A [ 88 ], and SYP [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified several complement system-related genes in AD. Among the 23 genes previous studies have shown their correlation with AD, we have: GFAP [ 41 , 42 ], PDGFRβ [ 43 45 ], NFKBIA [ 46 ], TNFRSF1B [ 47 ], NOTCH1 [ 48 ], BCL6 [ 49 ], CSF1R [ 50 ], LEP [ 51 ], DCLRE1C [ 52 ], KCNJ10 [ 53 ], MAP2K1 [ 54 ], VIP [ 55 ], SNCA [ 56 ], ENO2 [ 57 ], SST [ 58 ], UCHL1 [ 59 ], HPRT1 [ 60 ], STAT4 [ 61 ], CD14 [ 62 ], ITGB2 [ 63 ], SPP1 [ 64 ], STX1A [ 65 ], and SYP [ 66 ]. And these genes are involved in the regulation of molecules associated with the complement system, for instance, GFAP [ 67 ], PDGFRβ [ 68 ], NFKBIA [ 69 ], TNFRSF1B [ 70 ], NOTCH1 [ 71 ], BCL6 [ 72 ], CSF1R [ 73 ], LEP [ 74 ], DCLRE1C [ 75 ], KCNJ10 [ 76 ], MAP2K1 [ 77 ], VIP [ 78 ], SNCA [ 79 ], ENO2 [ 80 ], SST [ 81 ], UCHL1 [ 82 ], HPRT1 [ 83 ], STAT4 [ 84 ], CD14 [ 85 ], ITGB2 [ 86 ], SPP1 [ 87 ], STX1A [ 88 ], and SYP [ 89 ].…”
Section: Discussionmentioning
confidence: 99%